THE CONTRIBUTION RATIO OF THE KINEMATIC LAUNCH VECTORS AT THE MOMENT OF PERFORMING THE THROW PHASE AND ITS RELATIONSHIP TO THE ACHIEVEMENT OF HAMMER THROW PLAYERS FOR ADVANCED - Dr. Sabah Mahdi Salih; Dr. Hasanain Falah Hasan (Scholars Digest Publishing, 2024)
The importance of the research came from taking advantage of the values of the results of the kinetic analysis to identify the percentage of contribution of the kinematic launch vectors (launch speed - launch angle - launch point height) to the performance of the throwing stage and its relationship to the achievement of advanced hammer throw players by analyzing these variables and improving them to develop the athletic achievement. The research problem is that the effectiveness of the hammer throw is one of the athletics activities that depends to a large extent on the player's mastery of the stages of technical performance, as the performance includes multiple technical stages that overlap with each other and contain many critical and complex main points, which requires the player to perform them well in order to achieve the digital achievement. As for the research problem, through the researcher's observation of many different sports championships in athletics competitions, he noticed a weakness among players in performing the technical stages (swings, rotations, throwing position) and mastering them, especially the main ones, which is the final throwing stage of the hammer throw, which is a decisive stage to obtain the distance required by the player for the digital achievement, as it depends on the main and important kinematic variables, which are (the speed of the tool's launch, the angle of the tool's launch, the height of the tool's point) in this stage, which the thrower relies on to achieve the goal. Therefore, the researcher decided to study these three kinematic variables mentioned to know their relationship to the achievement and the extent of the percentage of their contribution in this stage through the results of the values of the analysis of the variables for them using kinetic analysis programs that are based on accurate scientific foundations to address the weakness in this stage (throwing the tool) and achieve the main goal of it, which is to achieve the farthest horizontal distance. For the hammer, the aim of the research is to identify the percentage of contribution of the kinematic launch vector variables (launch speed - launch angle - launch point height) at the moment of performing the throw phase and its relationship to the achievement of advanced hammer throw players. As for the research hypothesis, there is a percentage of contribution between the kinematic launch vectors (launch speed - launch angle - launch point height) at the moment of performing the throw phase with the achievement of advanced hammer throw players. The research method The researcher used the descriptive method using the correlation method to suit the nature of the research.
Keywords: Kinematic launch vectors, contribution ratio, throwing phase, hammer throw effectiveness.